Quantifying Epithelial Plasticity as a Platform to Reverse Epithelial Injury - Nishida, Kristine; Ghosh, Baishakhi; Chandrala, Lakshmana; Mahmud, Saborny; Chen, Si; Atulya Aman Khosla; Katz, Joseph; Sidhaye, Venkataramana K (bioRxiv, 2020)
Epithelial surfaces lining the lung serve as the primary environmental gaseous interface, and are subject to common life-limiting diseases, including COPD (Chronic Obstructive Pulmonary Disease). Despite the critical role of epithelial cells in pulmonary health and disease, quantitative models are lacking but are required given the large patient to patient variability to characterize the epithelial plasticity that follows injury. We have identified a series of quantitive assessments to measure the changes that occur in the epithelium and to identify targets that reverse injury. The injured epithelium has decreased ciliary function and monolayer height, which in the case of cells derived from COPD patients results in an overall disorganization of structure. Injury causes the cells to shift to an unjammed state, with corresponding increases in the velocity correlation length implicating cell shape and stiffness as fundamental to the injury response. Specific inhibitors of actin polymerization (LatA), of MAPK/ERK kinase (U0126) and Nrf-2 pathway activation (CDDO-Me) push the epithelium back towards a jammed state with decreased cell movement and correlation length, as well as improve barrier function and CBF. These studies attest to cell intrinsic properties that allow for a transition to an unjammed state, and that quantitative phenotypic analysis can identify potential specific pharmacologic targets in a given patient and provide insight into basic mechanisms of cellular damage.